Fertility and cancer (Swiss Medical Weekly, 2010)
Principles: Women of reproductive age with cancer fear for their childbearing potential as a result of the cancer itself and chemo- and/or radiation-therapy. Methods: Starting in 2006, a dedicated task force was set up at Lausanne University Hospital (CHUV) to handle all cancer and fertility issues and, in certain cases, offer access to emergency assisted reproductive technologies (ART) to preserve further childbearing options. Help provided by the task force was offered within a multidisciplinary framework encompassing psychological counselling offered to each patient or couple. Results: We report here the salient points of the experience gained through dedicated psychological counselling offered to cancer patients concerned about their future fecundity. This was done with the intention of underscoring the most clinically relevant lessons learned through our experience at CHUV. Conclusions: The specific ‘cancer and fertility’ counselling instituted at CHUV offers support for young women or couples confronted with stressful cancer and fertility issues. This type of specific counselling, the resource counselling, appears to be a particularly appropriate tool for patients abruptly involved in difficult decision-making processes under time constraints and thus extremely vulnerable. The personal feedbacks from the patients also confirm the importance of offering specific counselling and timely psychological support of the type reported here to all women of reproductive age before starting chemo- and/or radiation-therapy.